GLOBAL GENDER DISPARITIES IN EMPLOYMENT: INSIGHTS FROM THE ILO’S WORLD EMPLOYMENT AND SOCIAL OUTLOOK 2023 - James, Jaimol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines gender disparity in employment across regions using labour force data (ILO)from 117 countries, spanning 23 years (2000–2023). Gender disparity, defined as the difference between male and female employment levels, reflects significant inequality in global labour markets. A theoretical economic model is proposed to analyse gender disparity through key determinants, including policy frameworks, education levels, urbanization, and economic development. Advanced regression estimation techniques are employed to uncover significant predictors and their implications. The analysis reveals temporal and regional variations in gender disparity, emphasizing the urgent need for targeted policies to promote gender-inclusive labour markets.